Helicobacter pylori‐negative and non‐steroidal anti‐inflammatory drugs‐negative idiopathic peptic ulcers show refractoriness and high recurrence incidence: Multicenter follow‐up study of peptic ulcers in Japan. Issue 5 (3rd April 2016) - Kanno, Takeshi; Iijima, Katsunori; Abe, Yasuhiko; Yagi, Makoto; Asonuma, Sho; Ohyauchi, Motoki; Ito, Hirotaka; Koike, Tomoyuki; Shimosegawa, Tooru
Abstract : Background and Aim: Helicobacter pylori ‐negative and non‐steroidal anti‐inflammatory drugs (NSAIDs)‐negative idiopathic peptic ulcers (IPU) have attracted attention in Japan and other developed countries. The aim of the present study was to clarify the healing rate of IPU and the risk of recurrence. Methods: We conducted a retrospective follow‐up study of patients with peptic ulcer disease (PUD) who were diagnosed in our previous multicenter‐prospective study. Three hundred and eighty‐two patients from four institutions in the Tohoku district were enrolled. Enrolled subjects were divided into four groups according to H. pylori infection and intake of NSAIDs. In these patients, we checked treatment course, healing rate during 3 months, and recurrence rate. Results: Healing rates in the: (i) simple H. pylori group; (ii) H. pylori (+)/ NSAIDs (+) group, (iii) simple NSAIDs group; and (iv) IPU group, were 95.0%, 94.9%, 73.3%, and 77.4%, respectively. The healing rate of the IPU group was significantly lower than that of both the simple H. pylori group and the H. pylori (+)/ NSAIDs (+) group ( P < 0.01). The recurrence rate of 13.9% in the IPU group was much higher than the 2.1% in the simple H. pylori group ( P < 0.01). Additionally, the cumulative recurrence rates by the Kaplan–Meier method in the IPU group were significantly higher than those of the simple H. pylori group ( P = 0.015). Conclusion: We demonstrated that the clinical course of peptic ulcers is considerably different depending on the cause. IPU could be refractory to treatment and prone to recur compared with simple H. pylori ulcers.